Pengaruh Motivasi, Disiplin dan Kompensasi terhadap Kepuasan dan Kinerja Pegawai Badan Pusat Statistik (BPS) Provinsi Jambi - Gahara Haerani; Rahmat Muhammad; Tahir Kasnawi (Syntax Corporation, 2023)
The Central Bureau of Statistics is an institution established by national legislation to carry out public service activities, therefore the performance of BPS employees must be oriented at the public service by prioritizing superior service, caring and accompanied by adequate technical skills, this is to keep a balance with the progressively and better work climate. An institution often only requires high performance from its employees, without looking at the factors that influence their performance. But the basic factors in supporting performance such as work motivation, work discipline and job satisfaction must also be considered in order to increase employee productivity. This research was conducted to see how the influence of motivation, discipline and compensation/wages on satisfaction and performance of employees of the Central Bureau of Statistics (BPS) of Jambi Province. The method used in the analysis of this affect factor is using path analysis with the variables of Motivation, Discipline, and Compensation/Wages on the variables of Job Satisfaction and Employee Performance. The results showed a significant and positive effect between Motivation, Discipline, and Compensation/Wages on Job Satisfaction variables of 0.194, 0.164 and 0.682. While the effect of job satisfaction on employee performance is 0.275